Grazing Significantly Increases N2O Emission Rates in Alpine Meadows of the Tibetan Plateau - Li, Wei; Xu, Qingmin; Zhou, Huakun; Du, Yangong (Frontiers in Environmental Science, 2022)
Alpine meadows are robust nitrous oxide (N2O) sources that continually experience overgrazing on the Tibetan Plateau. However, the mechanisms underlying N2O fluxes are poorly understood. The effects of grazing activity on grassland N2O emission rates, soil and plant characteristics were investigated using a meta-analysis approach. This study revealed that the effect size of grazing was 0.31 ± 0.08 on N2O emission rates (P < 0.0001), and N2O fluxes increased by 36.27% than control. Light, moderate, and high grazing increased N2O emission rates by 34.62%, 19.48%, and 62.16%, respectively. The effect size of moderate grazing was significantly lower than that of high grazing (P < 0.05). The effect size of grazing on pH was significant (P < 0.05), and pH increased by 6.51% compared with control. Both soil ammonia and nitrate levels increased by 12.24% and 8.60%, respectively. However, grazing decreased soil total carbon, total phosphorus, and available phosphorus by 14.4%, 10.25%, and 10.15%, respectively. Grazing significantly decreased plant diversity (P < 0.05), richness, and aboveground biomass by 15.16%, 23.7%, and 30.7% (P < 0.01), respectively (P < 0.01). Aboveground biomass significantly influenced effect size on N2O emissions, explaining 13.36% of the variations. The direct coefficient of aboveground biomass on effect sizes was -0.631 based on the structural equation model. Although grazing significantly decreased aboveground biomass and diversity, moderate grazing is optimal for mitigating N2O emissions on the Tibetan Plateau.